Attracting Birds in the Texas Hill Country : A Guide to Land Stewardship - Stephens, W. Rufus (Book collections on Project MUSE., 2016)
"The book showcases 107 species in their habitats with color photographs and a short descriptive account of how to know the bird and care for its habitat. Three additional chapters on predator control, deer management, and cedar management offer detailed information on these special issues that impact the presence of birds throughout the region. By helping readers recognize and evaluate habitat health and then use appropriate habitat enhancement practices, the authors hope to inspire and enable widespread and effective bird conservation in the Texas Hill Country"--Provided by publisher.